2007
DOI: 10.1097/wnr.0b013e3282f0eb1c
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant effect of stem cell-derived monoaminergic grafts

Abstract: In this study, we demonstrate that embryonic stem cells can be engineered to differentiate into high percentages of serotonergic and dopaminergic neurons. In vitro, these cells release serotonin and dopamine in response to membrane depolarization. Upon engraftment into the medial prefrontal cortex in rats, the homolog of the human anterior cingulate cortex, the cells assumed neuronal morphologies, expressed monoaminergic-specific proteins, and seemed to functionally integrate, as assessed by the upregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The forced swim test, a conventional assay for assessment of FSL rat depressive-like behavior, 25,60 showed a significant reduction in immobility time after MSC treatment. Similarly, it was previously shown that monoaminergic grafts originating from embryonic stem cells decreased the immobility duration in forced swim tests after engraftment to the prefrontal cortex of Sprague-Dawley rats 61 . We also applied the dominant-submissive social behavior paradigm, in which the relative behavioral tendency toward submissiveness or dominance reflects the behavioral status on the axis between depression and mania.…”
Section: Discussionsupporting
confidence: 59%
“…The forced swim test, a conventional assay for assessment of FSL rat depressive-like behavior, 25,60 showed a significant reduction in immobility time after MSC treatment. Similarly, it was previously shown that monoaminergic grafts originating from embryonic stem cells decreased the immobility duration in forced swim tests after engraftment to the prefrontal cortex of Sprague-Dawley rats 61 . We also applied the dominant-submissive social behavior paradigm, in which the relative behavioral tendency toward submissiveness or dominance reflects the behavioral status on the axis between depression and mania.…”
Section: Discussionsupporting
confidence: 59%
“…Although affective neural networks are integrated with movement networks, analysis of graft effects on emotion is only beginning to be investigated. Our laboratory recently demonstrated in animal models that grafts of genetically-customized monoaminergic neurons can have an antidepressant effect and thus may be capable of modulating corticolimbic circuitry [2]. The present experiments demonstrate that a similar approach is feasible to study the neural circuitry associated with fear and anxiety.…”
Section: Discussionmentioning
confidence: 53%
“…With the advent of stem cell technology, the potential to replace injured or degenerative neurons needs to be explored. Several recent successes have encouraged further effort (Cunningham, et al 2007; Ren-Patterson, et al 2005; Vazey, et al 2006). …”
Section: Discussionmentioning
confidence: 99%